Parity funding of health care contributions in Germany: A DSGE perspective - Almira Enders; Dominik Groll; Nikolai Stähler (German Economic Review, 2020)
Germany reintroduced parity funding of the statutory health insurance scheme in January 2019 by lowering the contribution rates for employees and raising those for employers, leaving the total rate constant. This reduces the tax wedge between total labour costs and net wages. After a small demand impulse on impact, followed by a small downturn in the first two years after implementation, an estimated New Keynesian DSGE model indicates small positive long-run output and employment effects. However, the reduced tax wedge leads to lower public revenues. Aggregate macroeconomic and welfare effects will depend on how the government compensates for these revenue losses.
Keywords: E32; E24; F41; 330; tax incidence; social security contributions; DSGE modeling